Validation of Bengali version of functional digestive disorders quality of life questionnaire (Journal of Shaheed Suhrawardy Medical College, 2025)
Background: Most people have functional bowel disorders, and the most common ones are irritable bowel syndrome (IBS) and functional dyspepsia (FD). These disorders can make daily life very difficult. A lot of people use the Functional Digestive diseases Quality of Life Questionnaire (FDDQL) to measure the health-related quality of life (HRQOL) of people who have functional bowel diseases. However, there cannot be a Bengali form of FDDQL, even though it is accepted in many countries. The point of this study was to make a Bengali FDDQL that fits the culture and check its validity and reliability.Methodology: The survey questionnaire was initially written into Bengali and changed to fit the social and cultural situation in the area, as suggested by Beaton et al. At Dhaka Medical College, we looked at 130 people who had IBS and FD. We used updated kappa (k*) and item- and scale-level content reliability indices (I-CVI and S-CVI) to check the improved Bengali version. To prove convergent validity, Pearson's correlation values were used to look at the relationship between the FDDQL and the SF-36. Cronbach's alpha was used to measure internal uniformity. The patients were given the questionnaire 14 days after the first interview, and the coefficient of intraclass correlation was used to see how reliable the tests were when they were given again.Results: The six-step process for translating and adapting to different cultures did not find any major problems with the material or the language. The I-CVI was higher than 0.75, the k* was higher than 0.67, and the S-CVI was 0.91. A Pearson's association value of more than 0.74 showed that FDDQL and SF-36 were related in a good way. Strong internal concordance (Cronbach's alpha = 0.86) and high reliability among tests (ICC = 0.93) were shown for the scale.Conclusion: The Bengali version of the FDDQL works well, can be relied on, and is useful for measuring health-related quality of life in people with functional bowel diseases in both clinical and study settings.J Shaheed Suhrawardy Med Coll 2023; 15(2): 34-39